Lingguizhugan decoction enhances autophagy of Alzheimer’s disease via regulating the mTOR/ p70s6K pathway in vivo and in vitro - Xiaojing Chen; Qingrong Tian; Min Gao; Xibin Zhou; Chunxiang Zhou (Frontiers in Aging Neuroscience)
IntroductionLingguizhugan decoction (LGZG) has been reported to treat Alzheimer’s disease (AD) by anti-inflammatory and transporting amyloid-β (Aβ).MethodsUsing APP/PS1 transgenic mice as in vivo model and gave LGZG decoction by oral gavage. Using Aβ25-35-induced SH-SY5Y cells as in vitro model and then added LGZG medicated serum (LMS) to observe the regulatory effect of LGZG on AD autophagy-related pathways. Morris water maze (MWM) was used to evaluate the mice’s learning and memory ability. Mice’s hippocampus tissue sections were stained immunohistochemically to observe hippocampal Aβ deposition. Transmission electron microscopy monitored autophagosomes and autolysosomes. Western blot analysis measured protein expression levels of beclin-1, p62 and light chain 3II (LC3 II) and mTOR signaling. Results: LGZG could greatly improve learning and memory ability of APP/PS1 mice, and enhance autophagy in vitro and in vivo. LGZG increased the levels of beclin-1 and LC3 II and decreased the levels of p62.ConclusionLGZG enhanced autophagy and showed therapeutic potential in AD by inhibiting mTOR/p70s6K signaling.